Perforation of the anastomotic line post-truncal vagotomy and gastrojejunostomy - Basu, Shouptik (Indian Journal of Case Reports, 2018)
Peptic ulcer disease, that is refractory to medical management, must be managed surgically. A truncal vagotomy combined with a gastrojejunostomy or a pyloroplasty was a commonly done surgery in the past, along with drugs that control Helicobacter pylori infection. Gastrojejunostomy may be associated with several complications such as hemorrhage, perforation, retrograde intussusception, retroanastomotic hernia, adhesions, and gastrojejunocolic fistula. We report a case of an acute episode of spontaneous perforation of the gastrojejunostomy, which was done in the same patient 3 years back along with truncal vagotomy for a complicated duodenal ulcer with gastric outlet obstruction. We have also reviewed the literature associated with this rare case.